An inexpensive “smart” trap to capture nestbox-breeding owls and reduce sex biases in ringing data - Johan F Nilsson; Hannah Watson (Journal of Field Ornithology, 2025)
The ringing and controlling of previously marked birds are invaluable tools for studying the survival, productivity, and movement of birds. To maximize the value of ringing data, it is important to minimize any potential biases. For some species, such as nestbox-breeding owls, ringing records are typically heavily skewed toward females because they generally are easier to catch. The use of traditional mechanical nestbox traps can be vulnerable to false activation, incur lengthy disturbance and be labor-intensive to capture both members of a breeding pair. Here, we describe the design and construction of an inexpensive “smart” trap that provides a highly efficient method to capture nestbox-breeding owls and raptors. The trap is operated by a Raspberry Pi microcomputer and can send a text message to a designated phone number, allowing rapid retrieval of the captured bird and re-setting of the trap. From 2020 to 2023, using the smart trap, we successfully captured all the breeding male Tawny Owls Strix aluco in our study population. The trap also facilitated the capture of both adults of a breeding pair twice during the breeding season (to deploy and retrieve GPS loggers). By making this trap design openly available, we hope that more ornithologists will start to routinely catch male, as well as female, nestbox-breeding owls, thereby reducing the marked sex bias in ringing data. The trap can also be easily modified to facilitate capture of other nestbox-breeding birds and raptors.